Teacher ethics as a research problem: a narrative review of the scholarly writings - Bissembayeva, N.A.; Nurgaliyeva, S.A.; Ishanov, P.Z. (KU Publ., 2021)
The authors explore a vital problem of our time, i.e., the professional ethics of teachers. Considering the relevance of this problem, the authors of this paper initiated a study devoted to a narrative review of scientific sources of foreign authors from far and near abroad on teaching professional ethics to future teachers, synthesizing points of view on key aspects of this problem. The research was carried out by the method of systematization and generalization of pedagogical experience in the aspect of the issue under study, thus the authors of this work tried to bring experimental facts of scientific views of authors from far and near abroad into the system of observation. According to the results of interviews with graduate students, the majority of respondents have low indicators of knowledge and skills in the field of professional ethics by the end of university, which will have a negative impact on their future professional activities. The results of research will expand scientific knowledge on the problem of forming professional ethics among students-future teachers and complement the main provisions of professional ethics and concepts of moral and professional development of the individual, enriching the theory and methodology of continuing professional education.
Ғылыми мəселе ретіндегі кəсіби этика: ғылыми дереккөздерге сипаттамалы шолу
Профессиональная этика как научная проблема: описательный обзор научных источников
Keywords: ethics; higher school; professional ethics; formation, interviews; observations; teaching experience; theory and methodology